Triggering and evolution of a deep convective system in the Mediterranean Sea: modelling and observations at a very fine scale. (16th February 2017) - Fiori, E.; Ferraris, L.; Molini, L.; Siccardi, F.; Kranzlmueller, D.; Parodi, A.
Abstract : Gaining a deeper physical understanding of the high‐impact weather events which repeatedly affected the Western Mediterranean Basin in recent years on the coastal areas of eastern Spain, southern France and northern Italy is strongly motivated by the social request to reduce the casualties and the economical impacts due to these highly localized and hardly predictable phenomena. In October 2014, an extreme event hit Genoa city centre, less than 3 years after a very similar event, which occurred in November 2011. Taking advantage of the availability of both observational data and modelling results at the micro‐α meteorological scale, this article provides insights about the triggering mechanism and the subsequent spatio‐temporal evolution of the Genoa 2014 back‐building Mesoscale Convective System. The major finding is the effect of a virtual mountain created over the Ligurian Sea by the convergence of a cold and dry jet outflowing from the Po valley and a warm and moist low‐level southeasterly jet within the planetary boundary layer.